Letter to the editor: Western Trauma Association critical decision algorithm for the evaluation and management of traumatic pneumothorax. Issue 4 (3rd October 2022) - Kirkpatrick, Andrew W.; Coccolini, Federico; Parry, Neil; Roberts, Derek J.
Abstract : "Although we generally agree with the conclusions of the Western Trauma Association guidelines for the Evaluation and Management of Traumatic Pneumothorax, we believe further discussion of several critical points raised by these guidelines is necessary."